Developing eco-innovation in business practice in Slovakia - Vicianová, Jana Hroncová; Jaďuďová, Jana; Rolíková, Silvia (Journal of Business Economics and Management, 2017)
The paper presents the analyses and evaluates the current state of implementation of eco-innovation in the most energy-intensive sectors in Slovakia and also compares the eco-innovation performance of EU countries. Furthermore, it identifies the economic and environmental benefits from which businesses can profit following the introduction of this type of eco-innovation; it confirms the relationship between investments in environmental technologies and increasing sales of ecological products and services and identifies opportunities for development of eco-innovations in Slovakia. The industrial sectors in Slovakia have the potential to utilise eco-innovation throughout the structure of their economic activities, to develop new technologies and knowledge as well as in creating and developing partnerships, networks and mutual cooperation for the development of eco-innovation on the proviso that appropriate supporting eco-innovation policies and stimulus measures are in place. An analysis of the current state of eco-innovations in the selected enterprises was carried out on the basis of original empirical research which is based on a questionnaire survey on enterprises in the Slovak Republic.